Modelling of a three (single)-phase two-stage inversion power supply - Liu, Jin (2015)
In a more electric aircraft (MEA), the embedded electrical system utilize a broad range of power conversion for smooth and efficient power supply. This project aims to model and simulate a two-stage three-phase power inversion system to be employed in aircrafts for generating 115V/400Hz power. A full-bridge DC/DC converter with a built-in high frequency transformer is implemented at the primary stage of the system to enable isolation between the source and load terminals. And a three-leg full-bridge voltage source inverter modulated by space vector pulse width modulation (SVPWM) is developed at the secondary stage for efficient power inversion. The working principles of the converters as well as the procedures for implementing the SVPWM technique are elaborated in detail. A novel double closed loop control method is introduced to provide prompt response encountering disturbance in the input as well as sudden changes in the load. The power inversion system is modelled in MATLAB/Simulink and the circuit design and control methodology are validated by the simulation results. The robustness and effectiveness of the model is tested in various abnormal operation cases, and possible improvements are also discussed.